Elevated NK and T cell-associated cytokines in plasma are associated with serological response to influenza vaccination - Pickering, Harry; Carlock, Michael A.; Cappelletti, Monica; Gjertson, David W.; Ross, Ted M.; Reed, Elaine F. (Frontiers in Immunology, 2025)
IntroductionNumerous pre-vaccination factors are known to be associated with differential responses to influenza vaccination, including age, prior infection, vaccination history, immune cell frequencies, and transcriptomic profiles. However, plasma chemokines and cytokines are relatively unexplored. Given that older individuals have generally higher levels of inflammatory molecules in circulation, termed inflammaging, and also respond poorly to vaccination, plasma immune profiles likely play a role in effective response to influenza vaccination.MethodsA cohort of 100 people were sampled pre- (Day 0) and post-vaccination (Day 7) with the inactivated, quadrivalent Fluzone construct in the autumn of 2019 (UGA4). Plasma chemokines and cytokines were quantified by 38-plex Luminex assay, with ultrasensitive quantification of additional analytes by Single Molecule Array Technology (Simoa) assay. Antibodies against individual strains of influenza and serological response to vaccination were determined by Day 0 hemagglutination inhibition (HAI) titer and change in HAI titers from Day 0 to Day 28, respectively.ResultsAge was strongly associated with pre-vaccination HAI titers and differences in plasma analytes, but not changes in HAI titers post-vaccination. High plasma levels of eotaxin (CCL11) and MDC (CCL22) pre-vaccination were associated respectively with ineffective and effective serological response to vaccination. Increasing plasma levels of IFN-γ, IL-17A, and IL-15 from Day 0 to Day 7 post-vaccination were associated with effective serological response to vaccination.DiscussionIn conclusion, plasma chemokines and cytokine levels prior to or in the first few days post-influenza vaccination may be predictive of serological responses to vaccination, with changes in IFN-γ, IL-17A, and IL-15 post-vaccination possibly indicative of the activation of cell-mediated immunity. These findings support the need for larger, high-resolution studies exploring the role of plasma proteomics in serological responses to influenza vaccination.